1987
DOI: 10.1063/1.338410
|View full text |Cite
|
Sign up to set email alerts
|

Effects of heavy ion irradiation on amorphous hydrogenated (diamondlike) carbon films

Abstract: Energetic ion-beam irradiation of diamondlike carbon thin films induces a decrease of 5–6 orders of magnitude in the resistivity of the films from their as-grown value of 107 Ω cm. Diagnostics used to characterize the nature of the transformation included optical absorption measurements (band gap), Raman spectroscopy (microcrystalline structure), Rutherford backscattering spectroscopy (hydrogen content of the films), and measurements of the temperature dependence of the conductivity (electronic structure). It … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
29
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(31 citation statements)
references
References 26 publications
2
29
0
Order By: Relevance
“…Reductions in film resistivity with concomitant falls in the optical band gap as a function of ion dose were reported in ta-C by McCulloch et al, 13 and in diamondlike a-C:H by Prawer et al 14 In the former, the reduction of the optical gap and the decrease in film resistivity occurred even at the lowest doses investigated (10 13 cm Ϫ2 ), and appeared to be concomitant. In the latter study, the resistivity remained constant up to a dose of 10 15 cm Ϫ2 and then decreased, and the optical gap decreased from about 1.5 eV in the as-grown film to less than 1 eV (2ϫ10 17 cm Ϫ2 ), following the variation in the resistivity.…”
Section: Rapid Communicationsmentioning
confidence: 88%
See 3 more Smart Citations
“…Reductions in film resistivity with concomitant falls in the optical band gap as a function of ion dose were reported in ta-C by McCulloch et al, 13 and in diamondlike a-C:H by Prawer et al 14 In the former, the reduction of the optical gap and the decrease in film resistivity occurred even at the lowest doses investigated (10 13 cm Ϫ2 ), and appeared to be concomitant. In the latter study, the resistivity remained constant up to a dose of 10 15 cm Ϫ2 and then decreased, and the optical gap decreased from about 1.5 eV in the as-grown film to less than 1 eV (2ϫ10 17 cm Ϫ2 ), following the variation in the resistivity.…”
Section: Rapid Communicationsmentioning
confidence: 88%
“…These results indicate that there exist two regimes; one for doses up to and including 2ϫ10 14 cm Ϫ2 , where the Tauc gap remains constant and the film resistivity falls by about two orders of magnitude; and another regime above this dose where, by the highest dose of 2ϫ10 16 cm Ϫ2 , there is a near closure of the optical gap, a further reduction of the film resistivity by six orders of magnitude, and where exchange effects dominate the EPR linewidth and relaxation times. In order to analyze the resistivity variation, the equations for variable-range hopping ͑VRH͒ for electrons at the Fermi level, originally derived by Mott and Davis, 18 have been applied to these films.…”
mentioning
confidence: 84%
See 2 more Smart Citations
“…Cosmic rays are composed of highly energetic ions and electrons. Numerous works have been devoted to the study of energetic ions effect on hydrogenated carbonaceous matter by different diagnostic tools such as infrared or Raman spectroscopy, or techniques allowing one to measure the hydrogen content (e.g., Baumann et al 1987;Prawer et al 1987;González-Hernández et al 1988;Fujimoto et al 1988;Ingram & McCormick 1988;Zou et al 1988;Adel et al 1989;Marée et al 1996;Pawlak et al 1997;Som et al 1999;Baptista et al 2004;Som et al 2005;Brunetto et al 2009). It is observed that the irradiation of these materials results in a decrease of the aliphatic C-H spectral signatures and of the hydrogen content.…”
Section: Introductionmentioning
confidence: 99%